Review : The Characteristics of Genetic Resource of Bali Cattle (Bos-bibos banteng) and the Alternative of It's Conservation Methods - Gunawan, Ria Setia Lestari; Arifin, Johar; Dudi, Dudi (Jurnal Produksi Ternak Terapan, 2026)
Bali cattle are an indigenous Indonesian beef breed that originated from the domestication of the Banteng (Bos-bibos banteng). A major challenge in their development is the breed’s low quality, which is believed to result from inbreeding and suboptimal management practices. Genetic and crossbreeding impacts often lead to losses such as reduced endurance, fertility, and birth weight. In response, the government has made efforts to introduce high-quality bulls into breed source areas, regulate cattle release including controlling the culling of productive female cattle, and accurately monitor the number of Bali cattle released to maintain population balance. Consequently, conservation efforts through both in-situ and ex-situ methods are essential. This study indicates that documentation, reproductive and production evaluations, and initiatives to improve Bali cattle’s genetic quality in Indonesia have been conducted, although these efforts remain limited in scope.